Optimization of Grading Ring Design for Metal Oxide Arrester Using Gravitational Search Algorithm - Illias H.A.; Zern Hong C.; Aramugam K.; Mokhlis H.; Ariffin A.M.; Fairouz Mohd Yousof M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Birds; Electric fields; Genetic algorithms; Grading; Learning algorithms; Metallic compounds; Metals; Particle swarm optimization (PSO); Rings (components); Simulated annealing; Surge protection; Comsol multiphysics; Electric field magnitude; Grading rings; Gravitational search algorithm (GSA); Gravitational search algorithms; Metal oxide arrester; Optimization method; Optimum designs; Dielectric materials